Konsep Nafs Dalam Bahasa Arab Dan Relevansinya Bagi Psikoterapi Islam Modern - Lenni Suriyanti; Muhammad Amri; Darussalam Syamsuddin; Amiruddin (CV. SINAR HOWUHOWU, 2026)
The study of Arabic language and literature during the medieval period offers a deep understanding of the intellectual and cultural dynamics of Arabic that formed the foundation of the development of modern Arabic language and literature. This study aims to analyze aspects of medieval language and literature by covering political conditions and their influence on literary production, the development of historiographic works, the emergence of the encyclopedia genre, the biographical tradition (tarājim), the role of language scholars, and the phenomenon of the decline of classical literature. The method used is a library study with a historical-descriptive approach and comparative textual analysis. The results of the study show that the fragmented political conditions in the medieval period gave rise to a diverse intellectual environment, which triggered the growth of historiography, encyclopedism, and biographical writing as an effort to document and legitimize intellectually. The role of language scholars in the process of codifying nahwu, lexicography, and balaghah helped strengthen the standard of Arabic language that has survived into the modern era. On the other hand, the tendency of decline in classical literature, especially in poetic creativity, actually opened up space for the birth of modern literary innovation in the 19th and 20th centuries. Overall, these findings confirm that the legacy of medieval Arabic language and literature has significant implications for the formation of the linguistic and aesthetic identity of modern Arabic literature, both as an inherited model and as a starting point for contemporary literary renewal.